The effect of bay leaf extract (Syzygium polyanthum) on vascular endothelial growth factor (VEGF) and CD31 (PECAM-1) expression in acute coronary syndrome - Refli Hasan; Siregar Gontar Alamsyah; Dharma Lindarto (Medicinski glasnik, 2020)
Aim: To investigate effect of bay leaf extract in endothelial integrity, observed by vascular endothelial growth factor (VEGF) level, VEGF and CD31 expression. Methods: Thirty-two acute coronary syndrome surgery-induced Wistar Rats (Rattus novergicus) were divided into 16 bay leaf extract (treatment) groups and 16 control groups, sacrificed on day 1, 4, 7, and 14 after the induction. Serum VEGF level was determined by ELISA and expression of VEGFR-2 and CD31 were detected on immunohistochemistry. Results: This study showed increased expression of serum VEGF level, and VEGFR-2 expression was found significantly on day 7 and 14 in the treatment group compared to the control group. CD31 expression was significantly different compared to the control groups on day 4, 7, and 14 of administration. Conclusion: The potential effect of bay leaf extract on angiogenesis in acute coronary syndrome (ACS) as adjuvant for the treatment. Bay leaf extract has been shown to support angiogenesis and maintain endothelial integrity that leads to better prognosis for reperfusion on ischemic tissue.
Keywords: ischemia; flavonoids; herbal medicine